Nurses’ Role in Completing Anamnesis Supporting Coding of External Cause Injury Diagnoses - Andi karisma Nurdiyansyah; Deby Zulkarnain Rahadian Syah; Ida Aninda; Ragil Lintang Juliana; Gebi Yulanda; Piping Asgiani; Nik Azliza Nik Ariffin (Jurnal Infokes, 2026)
The accuracy of ICD-10 external cause injury coding depends heavily on the completeness of anamnesis documentation, particularly information on event chronology, place of occurrence, and patient activity. Nurses, as primary healthcare professionals responsible for anamnesis documentation in the Emergency Department (ED), play a key role in supporting accurate diagnostic coding. However, incomplete documentation of external cause injury information remains a common challenge in hospital settings. This study aimed to analyze the role of nurses in ensuring the completeness of external cause injury anamnesis to support accurate diagnostic coding at Mitra Paramedika Hospital, Yogyakarta. A qualitative descriptive study with a case study approach was conducted involving 12 healthcare workers, consisting of 10 emergency nurses and 2 medical record coders. Data were collected through pre-tests, focused group discussions (FGDs), post-tests, medical record observations, and in-depth interviews. Descriptive analysis was used to assess changes in knowledge and documentation practices before and after the intervention. The results indicated that prior to the FGD, several nurses had limited understanding of the importance of documenting place of occurrence and patient activity for external cause coding. Following the FGD, all participants demonstrated adequate knowledge in the post-test. Additionally, the use of electronic medical records improved documentation readability and completeness, facilitating more accurate coding. This study concludes that nurses play a critical role in external cause injury documentation, and that educational interventions and electronic medical record implementation effectively enhance documentation quality and coding accuracy.